2014
DOI: 10.1080/09593330.2014.970584
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal composition in stormwater and retention in ponds dependent on pond age, design and catchment type

Abstract: Heavy metals have toxic effects on flora and fauna in the aquatic environments and are of great concern in stormwater. Heavy metal runoff was studied in 37 stormwater ponds in Denmark with varying heavy metal load, catchment type and pond design. The studied metals were Cu, Cr, Cd, Pb, Ni and Zn. The concentrations varied considerably depending on the catchment type, with the highest concentrations coming from industrial areas and the lowest from uncultivated and rural areas. Ponds can effectively remove heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
6
22
0
Order By: Relevance
“…In contrast, low inflow concentration of Cr (6.9 ± 2.5) μg L −1 , and Cd (0.7 ± 0.2 μg L −1 ) was observed. In comparison, Egemose et al investigated heavy metal composition in stormwater and retention ponds, and reported an inflow concentration of 13 ± 7 μg L −1 for Cu, 16 ± 2 μg L −1 for Cr, 2 ± 3 μg L −1 for Cd, 14 ± 38 μg L −1 for Pb, 4 ± 15 μg L −1 for Ni, and 29 ± 10 μg L −1 for Zn. The presence of these metals in stormwater may be caused by: i) vehicle brake emissions for Cu; ii) tire wear for Zn; and iii) atmospheric deposition for Cu and P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, low inflow concentration of Cr (6.9 ± 2.5) μg L −1 , and Cd (0.7 ± 0.2 μg L −1 ) was observed. In comparison, Egemose et al investigated heavy metal composition in stormwater and retention ponds, and reported an inflow concentration of 13 ± 7 μg L −1 for Cu, 16 ± 2 μg L −1 for Cr, 2 ± 3 μg L −1 for Cd, 14 ± 38 μg L −1 for Pb, 4 ± 15 μg L −1 for Ni, and 29 ± 10 μg L −1 for Zn. The presence of these metals in stormwater may be caused by: i) vehicle brake emissions for Cu; ii) tire wear for Zn; and iii) atmospheric deposition for Cu and P.…”
Section: Resultsmentioning
confidence: 99%
“…Trace metals (e.g., Cu and Zn) are biologically important. They are micronutrients required for the growth of many aquatic organisms . However, at high concentrations, metals such as Pb, Cr, and Cd are very toxic.…”
Section: Resultsmentioning
confidence: 99%
“…PP and PFe were measured by boiling the combusted filter in 1 M HCl (1 h) followed by determination of dissolved inorganic phosphorus (DIP) and dissolved iron (DFe) in the extract (Andersen, 1976). The remaining two filters were kept for analysis of heavy metals (Egemose et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The stream stations are evenly distributed in the area, represented as black dots in Figure 1B. GIS themes with information about stormwater outlet locations in the streams were divided into wastewater overflows from combined sewers (77) and outlets from separate sewers (319), and location of stormwater ponds (110) and water quality parameters were included [25,26]. GIS themes with information about catchment areas and land use (divided into "nature", which covers moors, meadows, coastal meadows, commons, heaths, lakes, and streams; "forest", which covers conifer trees and deciduous trees; "urban areas"; "freshwater"; and "agriculture") as well as location of stormwater outlets and sewage catchment areas (622 stations) were constructed.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, scattered houses in the studied area (3837 properties) were also included in a theme. All available data regarding catchment types, streams quality, and stormwater handling in the studied area were collected [25,26]. The local utility company Arwos (Aabenraa, Denmark) provided all technical data and maps concerning urban stormwater outlets.…”
Section: Methodsmentioning
confidence: 99%